Membangun Sumber Daya Manusia Berkarakter Melalui Metode Pendidikan Karakter - Mahardani, Ahmad Subhan; Basalamah, Muhammad Ridwan (JU-ke: Jurnal Ketahanan Pangan, 2018)
The quality of human resources (HR) owned by a nation is also determine the quality and competitiveness of a nation. Developed countries in the World, such as Japan, China, do not actually have abundant natural resources, because they have strong human resources they are transformed into giant countries in a world that is so competitive Strong in the world. This study aims to determine the role of prime character education methods at basic education institutions in Malang, in realizing quality human resources. This research model is expected to help know the factors that influence the effectiveness of character education method in the basic education institution in realizing the human resources character. The population in this research is the teacher in elementary school in Malang, namely SD Islam Sabilillah, SD Anak Saleh, and Madrasah Ibtidaiyah Negeri 1 (MIN). The result of the research shows that from the six indicators of character education method, five of them are assignment, habituation, training, learning, direction, influence to the realization of human resources characterized. While the exemplary indicator in this research does not have an influence on the formation of human resources character. That is, the method of character education is a powerful method to internalize the values of noble and noble characters for the formation of Human Resources character, because in it there are elements of habituation important to embed in each individual.Â Keyword : Â Human Resource Management, Educational Character, Educational Character Method